Admisión temporal y control fronterizo: Análisis comparado y recomendaciones para la regulación de vehículos turísticos en Ecuador - Cajamarca Carrion, Jessica Paola; Parrales Loaiza, Mario Atilio (Machala : Universidad Técnica de Machala, 2025)
This article analyzes the irregular presence of private tourist vehicles with expired permits at the Huaquillas border crossing (Ecuador) and its impact on foreign trade logistics and tourism dynamics between 2021 and 2024. The objective is to analyze irregularities in the presence of tourist vehicles at the Huaquillas border between 2021 and 2024, using a qualitative approach based on regulatory review, audits by the Comptroller's Office, and official statistics. Regulatory gaps, deficiencies in customs traceability, and limited inter-institutional coordination are identified. Based on a comparison with experiences in Peru and Colombia, recommendations are proposed to improve regulation, control, and coordination between entities. Consequently, the proposal is to modernize the temporary admission regime through interoperable platforms, ongoing training, and a deterrent sanctioning scheme. The findings serve as input for designing public policies that strengthen Ecuador's trade competitiveness and border governance.
El artículo analiza la permanencia irregular de vehículos de uso privado del turista con permisos vencidos en el paso fronterizo de Huaquillas (Ecuador) y sus repercusiones sobre la logística del comercio exterior y la dinámica turística entre 2021 y 2024. El objetivo es analizar las irregularidades en la permanencia de vehículos de turistas en la frontera de Huaquillas, entre los años 2021 y 2024, mediante un enfoque cualitativo, sustentado en revisión normativa, auditorías de la Contraloría y estadísticas oficiales, se identifican vacíos regulatorios, deficiencias en la trazabilidad aduanera y una coordinación interinstitucional limitada. A partir de la comparación con experiencias de Perú y Colombia, se proponen recomendaciones orientadas a mejorar la regulación, el control y la coordinación entre entidades. En consecuencia, se propone modernizar el régimen de admisión temporal mediante plataformas interoperables, capacitación continua y un esquema sancionatorio disuasorio. Los hallazgos sirven de insumo para diseñar políticas públicas que refuercen la competitividad comercial y la gobernanza fronteriza de Ecuador.
Keywords: RÉGIMEN DE ADMISIÓN TEMPORAL; CONTROL FRONTERIZO; HUAQUILLAS; COMERCIO EXTERIOR